ANALISIS STRATEGI PT APAC INTI CORPORA DIINDUSTRI TPT - , Nurma Febrina, Bambang Riyanto L.S., MBA, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The intensification of rivalries in the Textile industry (TPT) and the continuous demand to provide higher quality, (technology) at competitive prices, are driving more companies to engage in vying for a superior product. This research thus brings forth the question as to whether PT Apac Inti Corpora (AIC) are sufficiently competent to compete and maintain its position as the market leader in the industry with its current strategic plan. The objective of this research therefore, is to evaluate AIC current strategic planning and to observe situation analysis (internal and external) of the Textile industry in order to draw a hypothetical conclusion to examine the current AIC strategy: The effectiveness of AIC current strategic planning and its application to the current market place while providing alternative strategies to boost the competitiveness of the Indonesian Textile industry. Some functional aspects, namely the marketing, financial, operational and human resource were observed to analyze the internal environment of the company. In the external analysis, characteristic industry analysis, the Porter five forces, Driving Forces, and Key Success Factors were examined, determinants to anticipate challenges while maximizing opportunities and evaluate performance in achieving the companyâs strategic goals In the Indonesian Textile industry. Finally, the analyze the companyâs strength, weaknesses as well as the opportunities and threats in order to define actions the company needed in order to achieve its strategic goals given the companyâs resources.